Pengaruh Kepuasan Konsumen, Influencer Marketing, dan Varian Produk terhadap Keputusan Pembelian Produk So Nice - Pratama, Yuko Kurnia; Aqmala, Diana; Sukono Putra, Febrianur Ibnu Fitroh (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of customer satisfaction, influencer marketing, and product variety on purchasing decisions for So Nice products. A quantitative approach was employed, using an online survey questionnaire distributed to respondents. Purposive sampling was used with criteria: respondents aged 17 years or older, having purchased So Nice products, and aware of So Nice advertisements featuring Asnawi Mangkualam. A total of 160 respondents participated, and the data were analyzed using classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results showed that all three independent variables positively and significantly influence purchasing decisions. Customer satisfaction had the greatest, followed by product variety, and influencer marketing. These findings highlight the importance of product quality, diverse product offerings, and relevant marketing strategies in enhancing consumer purchasing decisions. Based on these findings, it is recommended that So Nice improve product quality and innovate new flavors that align with local market preferences. Marketing strategies using influencers should focus on credible figures in the culinary field. Future research is encouraged to explore other variables such as pricing and customer loyalty to broaden insights into consumer purchasing behavior.